Anabolic steroids and cardiovascular risk: A national population-based cohort study. (1st July 2015) - Thiblin, Ingemar; Garmo, Hans; Garle, Mats; Holmberg, Lars; Byberg, Liisa; Michaëlsson, Karl; Gedeborg, Rolf
Highlights: This is a nation wide population study. We examine cardiac events and general mortality in anabolic androgenic steroids (AAS) users. Our results suggest that use of anabolic steroids is an independent risk factor for cardiac disease. Abstract: Background: Non-therapeutic use of anabolic androgenic steroids (AAS) has been associated with various adverse effects; one of the most serious being direct cardiovascular effects with unknown long-term consequences. Therefore, large studies of the association between AAS and cardiovascular outcomes are warranted. We investigated cardiovascular morbidity and mortality in individuals who tested positive for AAS. Methods and results: Between 2002 and 2009, a total of 2013 men were enrolled in a cohort on the date of their first AAS test. Mortality and morbidity after cohort entry was retrieved from national registries. Of the 2013 individuals, 409 (20%) tested positive for AAS. These men had twice the cardiovascular morbidity and mortality rate as those with negative tests (adjusted hazard ratio (aHR) 2.0; 95% confidence interval (CI) 1.2–3.3). Compared to the Swedish population, all tested men had an increased risk of premature death from all causes (standardized mortality ratio for AAS-positive: 19.3, 95% CI 12.4–30.0; for AAS-negative: 8.3, 95% CI 6.1–11.0). Conclusion: Non-therapeutic exposure to AAS appears to be an independent risk factor for cardiovascular morbidity and premature death.